Outcome of patients with mantle cell lymphoma after autologous stem cell transplantation in the pre‐CAR T‐cell era. Issue 2 (5th December 2021) - Mathys, Anina; Bacher, Ulrike; Banz, Yara; Legros, Myriam; Mansouri Taleghani, Behrouz; Novak, Urban; Pabst, Thomas
Abstract: Mantle cell lymphoma (MCL) patients can be treated with intensive induction therapy, followed by high dose chemotherapy (HDCT) with autologous stem cell transplantation (ASCT) for consolidation and subsequent anti‐CD20 maintenance. For patients relapsing after bruton tyrosine kinase (BTK) inhibitors, CAR T‐cell therapy became available in late 2020 fueling the interest in outcomes of relapsing MCL patients. We retrospectively analyzed the outcome of MCL patients receiving HDCT/ASCT at our center between 2000 and 2021, thus, before availability of CAR‐T cells. We identified 97 MCL patients undergoing HDCT/ASCT in this period with a median follow‐up of 52 months. 43 (44%) patients ultimately relapsed, and 29 (30%) have died. The median progression‐free survival (PFS) for the entire cohort was 48 months and overall survival (OS) was 202 months. Relapsing patients had a median PFS of only 28 months and median OS of 105 months. The OS of relapsing patients receiving BTK inhibitors was 148 versus 78 months in patients who never received BTK inhibitors ( p  = 0.1175). Even after HDCT/ASCT, a substantial proportion of MCL patients will relapse and ultimately die of the disease, emphasizing the need for new therapeutic options including CAR T‐cell treatment for this lymphoma subtype.